2017
DOI: 10.4103/jcd.jcd_233_16
|View full text |Cite
|
Sign up to set email alerts
|

Influence of root canal obturation using gutta-percha with three different sealers on root reinforcement of endodontically treated teeth. An in vitro comparative study of mandibular incisors

Abstract: Aim:The purpose of this in vitro study was to evaluate the vertical force required to fracture mandibular incisor teeth, obturated using gutta-percha with three different sealers.Materials and Methods:Seventy-five extracted mandibular incisors with intact and fully formed apices, exhibiting single root and canal were acquired. The teeth were decoronated obtaining a root segments of 15 mm and were divided into five groups (n = 15). Group 1: left uninstrumented and unfilled (negative control). For groups 2–5, sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 23 publications
2
6
1
1
Order By: Relevance
“…This was in agreement with earlier studies ( 10 , 11 ). In contrast to what was shown by three studies, which found that bioceramic-based sealers had statistically improved the fracture resistance of teeth ( 5 , 9 , 12 ).…”
Section: Discussioncontrasting
confidence: 91%
“…This was in agreement with earlier studies ( 10 , 11 ). In contrast to what was shown by three studies, which found that bioceramic-based sealers had statistically improved the fracture resistance of teeth ( 5 , 9 , 12 ).…”
Section: Discussioncontrasting
confidence: 91%
“…This chemical bonding along with the deep penetration of the sealer into canal irregularities and dentinal tubules enhances the fracture resistance of teeth (33,34) . So, calcium silicate root canal sealers might have the potential to reinforce the instrumented teeth against vertical root fracture (35,36) .…”
Section: Discussionmentioning
confidence: 99%
“…Our study findings agree with the findings of Dibaji et al, which demonstrated improved fracture resistance for AH+ and then bioceramic-based endodontic sealers such as TotalFill BC sealer [ 11 ]. Some other studies have shown superior fracture resistance for bioceramic-based endodontic sealers compared to AH+ sealers [ 4 , 12 ]. Additionally, Topcuolu et al showed a higher bioceramic FR, despite the fact that the difference between the groups failed to achieve statistical significance [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endodontic obturation materials bond to the radicular dentin and may help improve the FR of the obturating materials [ 3 ]. When instrumented but not obturated canals are compared to sealers and lateral condensation, the roots are significantly strengthened [ 4 ]. Resilon and Gutta Percha root canal fillings, which have a lower modulus of elasticity than dentine, have little or no root-strengthening capacity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%